Ferroelectric phase formation for undoped ZrO2 thin films by wet O2 annealing. (7th April 2020) - Shibayama, Shigehisa; Nagano, Jotaro; Sakashita, Mitsuo; Nakatsuka, Osamu
Abstract: Herein, the impact of wet O2 annealing on the phase transition of ZrO2 thin films was investigated and compared with the impact on phase transition of HfO2 thin films. The results showed that wet O2 annealing to crystallized ZrO2 and HfO2 dramatically promoted the phase transition from tetragonal ( t ) to orthorhombic ( o ) to monoclinic ( m ) compared with dry O2 annealing. In addition, the ferroelectric phase of approximately 17-nm thick ZrO2 films was formed without m -phase formation by wet O2 annealing, and the ferroelectricity of ZrO2 was found to be independent of wet O2 annealing temperature. The switchable polarization ( P SW ) and the coercive field ( E C ) were approximately 6 μ C cm −2 and 1.5 MV cm −1, respectively. Furthermore, larger P SW was obtained for thinner ZrO2 films. Finally, we discussed the possible approaches to further promote the t → o -phase transition for ZrO2 thin films by wet O2 annealing.